EVALUASI RISIKO KESELAMATAN DAN KESEHATAN KERJA PADA PROYEK INSTALASI PIPANISASI DI PT EFE BERBASIS METODE JSA DAN HIRARC - Wiryawan, Muhammad Ricky; Mahbubah, Nina Aini (Fakultas Teknik, Universitas Riau Kepulauan, 2024)
Work accidents occur in the work environment, which can occur due to unsafe work environment conditions or human error. PT TKA is a construction services company located in the Gresik Regency, and its work specifications use fiberglass and HDPE materials. In the work activities carried out by PT TKA, several unsafe actions or unsafe conditions were found which caused accidents. This research aims to evaluate the dangers and causes of danger based on the conditions and activities of pipe installation projects based on the risk of unsafe actions and conditions. Job Safety Analysis, Hazard Identification, Risk Assessment, and Risk Control were used as research methods. The research respondents were five expert employees on pipeline projects. The research showed that eleven stages of pipe installation project work were identified, resulting in small, medium, and large-scale hazard risks. The research results show that unsafe conditions dominate the occurrence of danger and the risk of work accidents.